Perancangan Aplikasi SARAMA Untuk Siswa Yayasan Al-Bayyinah - Muhammad Nasser Akbar; Narti Narti; Rangga Pebrianto (Evolusi : Jurnal Sains dan Manajemen, 2026)
Learning technology provides new opportunities to improve the effectiveness of learning, especially in early childhood Islamic religious education. In practice, the Al-Bayyinah Foundation still faces limitations in interactive learning media that are able to attract children's interest in the process of learning religious materials, including memorizing ablution and prayer recitations, so that learning still tends to be carried out conventionally. This study aims to create an innovation, namely designing and developing interactive learning media as a supporting medium for memorizing ablution and prayer recitations for children. The research methods used include the design stage, application development, and testing system functionality. The results of the study are in the form of the SARAMA application for interactive learning equipped with features for memorizing ablution materials, memorizing prayers, quizzes, as well as interesting visual and audio elements.